Ex vivo assessment of surgically repaired tibial plateau fracture displacement under axial load using large-volume micro-CT. (November 2022) - Bennett, Kieran J.; Callary, Stuart A.; Atkins, Gerald J.; Martelli, Saulo; Perilli, Egon; Bogdan Solomon, L.; Thewlis, Dominic
Abstract: Postoperative weight bearing has the potential to generate fragmental motion of surgically repaired tibial plateau fractures (TPFs), which may contribute to loss of fracture reduction. The effect of loading on the internal distribution of fragmentary displacements is currently unknown. The aim of this study was to determine the internal displacements of surgically repaired split TPFs due to a three-bodyweight load, using large-volume micro-CT imaging and image correlation. Fractures were generated and surgically repaired for two cadaveric specimens. Load was applied to the specimens inside a large-volume micro-CT system and scanned at 0.046 mm isotropic voxel size. Pre- and post-loading images were paired, co-registered, and internal fragmentary displacements quantified. Internal fragmental displacements of the cadaveric bones were compared to in vivo displacements measured in the lateral split fragments of TPFs in a clinical cohort of patients who had similar surgical repair and were prescribed pain tolerated postoperative weight bearing. The split fragments of cadaveric specimens displaced, on average, less than 0.3 mm, consistent with in vivo measurements. Specimen one rotated around the mediolateral axis, while specimen two displaced consistently caudally. Specimen two also had varying displacements along the mediolateral axis where, at the fracture site, the fragment displaced caudally and laterally, while the most lateral edge of the tibial plateau displaced caudally and medially. The methods applied in this study can be used to measure internal fragmental motion within TPFs.